Innovations as a Factor for Ensuring Economic Safety - Maxim SANDU; Lilia ŞARGU; Alexandr GRIBINCEA (Eastern European Journal of Regional Studies)
In modern conditions of development of the competitive environment, one of the main ways to solve economic, social and environmental problems is to use the latest achievements of science and technology. Each enterprise seeks to ensure that economic growth is intense, i.e. to be a consequence of the application of more sophisticated factors of production and technology. The prerequisite for intensive growth is the use of innovative strategy in the practical activities of enterprises. The end result of innovations is the materialization and industrial development of innovation, the idea of which can be the scientific and technical activity, and marketing research to identify unmet needs. The innovations are an effective defensive reaction of the firm to the emerging threats of losing market place, constant pressure from competitors, the challenge of new technologies, shortening the life of products, legislative restrictions and changing the market situation. In the offensive version, the innovation is a mean of exploiting new opportunities to preserve or gain a competitive advantage. In the long term aspect, the company has no choice but to pursue an innovation policy, which is the only source of lasting success. The main objective of researching the innovation activity of any organization is to ensure competitiveness in market conditions in order to identify risk factors and ways to overcome them.